Usefulness of body composition assessment by bioelectrical impedance vector analysis in subacute post-stroke patients in rehabilitation - Alessandro Guerrini; Mariacristina Siotto; Carola Cocco; Marco Germanotta; Valeria Cipollini; Laura Cortellini; Arianna Pavan; Stefania Lattanzi; Sabina Insalaco; Yeganeh Manon Khazrai; Irene Giovanna Aprile (Scientific Reports)
Abstract Bioelectrical Impedance Vector Analysis (BIVA) is a valuable tool for evaluating hydration and body composition, but its application in subacute post-stroke patients remains unexplored. This study aimed to fill this gap by analyzing BIVA in a cohort of 87 subacute post-stroke patients (42 women, mean age 69 ± 12) undergoing rehabilitation. At admission (T0), diagnosis of malnutrition with GLIM criteria and of sarcopenia with EWGSOP2 was done, and patients were analyzed with BIVA. The change in modified Barthel Index (mBIT1-mBIT0) was assessed to evaluate the improvement in functional recovery. BIVA revealed that both adult patients (< 65 years, n = 29) and elderly patients (≥ 65 years, n = 58) exhibited high body fluid overload and low muscle mass. Additionally, BIVA revealed a significant rightward shift of the bioimpedance vectors in malnourished (n = 37) versus non-malnourished patients (T2 = 56.9, p < 0.001, D = 1.68) and in sarcopenic (n = 24) versus non-sarcopenic patients (T2 = 36.4, p < 0.001, D = 1.5). Lastly, the BIVA distinguished patients with greater improvement (n = 53) from patients with lower improvement (n = 34) (T2 = 10.6, p = 0.007, D = 0.7). In conclusion, BIVA is an effective, easy-to-use tool for evaluating hydration, nutritional status, and recovery in post-stroke rehabilitation.